P183 How likely is environmental contamination of Chlamydia trachomatis DNA to lead to false positive results in patients attending our clinic?. (23rd May 2012) - Chan, S Y; King, R; Borgulya, G; Pakianathan, M; Sadiq, S T; Hay, P; Planche, T
Abstract : Background: Environmental contamination with DNA from Chlamydia trachomatis (CT) has been reported from GUM clinics, suggesting the possibility of cross contamination of specimens during sample processing or the environment. If it does occur, contamination is likely dependent to some degree on how busy patient throughput is in a clinic. Our GUM clinic sees over 29 000 patients a year. Aims: To investigate whether diagnostic samples could become contaminated from the environment in our clinic. Methods: We investigated the potential for contamination in two ways. (1) A dummy run of 60 sterile water samples, as surrogates of urine and 10 sterile swabs during routine clinic times. (2) A patient throughput study using logistic regression analysis to see if patients positive for CT were associated with attendance numbers. We hypothesise that possible contamination increases after each infected patient and drops off to zero over the weekend. Our clinic is open from Monday to Friday and cleaned daily. Toilets are not cleaned between patients. Results were analysed for walk in clinics. Results: None of the dummy urine or swabs tested positive for CT over 6 months. In a year, 24 115 patients attended the walk in clinics with 2860 (11.9%) testing positive for CT. A logistic regression analysis was done on CT positivity on Mondays compared to Tuesdays to Fridays. This was adjusted for age, gender, sexuality and type of clinic. Rates of CT were 5% higher on Tuesdays through Fridays than on Mondays but the difference was not significant (95% CI 0.95 to 1.16). Conclusion: There was no evidence of dummy sample contamination during our study period. We found weak association between CT positivity and clinic attendance although it was not significant at the 5% level. Further studies with a larger sample size and analysis on within day trends could explore this in depth. Environmental CT is unlikely to lead to false positive results in our clinic.